Modeling in biopharmaceutics, pharmacokinetics, and pharmacodynamics : homogeneous and heterogeneous approaches /: homogeneous and heterogeneous approaches. ([2016]) - Macheras, P (Panos); Iliadis, Athanassios
No abstract available